Effects of different manganese precursors as promoters on catalytic performance of CuO–MnOx/TiO2 catalysts for NO removal by CO. Issue 24 (28th June 2015) - Sun, Chuanzhi; Tang, Yingjie; Gao, Fei; Sun, Jingfang; Ma, Kaili; Tang, Changjin; Dong, Lin
<x xml:space="preserve">Abstract</x> Since the formation of the surface synergetic oxygen vacancy SSOV (Cu+–□–Mn3+) in the xCuyMn(N)/TiO2 catalyst is easier than that (Cu+–□–Mn2+) in the xCuyMn(A)/TiO2 catalyst, the activity of the xCuyMn(N)/TiO2 catalyst is higher than that of the xCuyMn(A)/TiO2 catalyst.